Nutritious underutilized species - Taro - Alercia, A.; Bioversity International (2013)
Colocasia esculenta, commonly known as taro, is a staple vegetable crop that has been used as food for over 9,000 years, making it one of the world’s oldest food crops. It is used as a source of protein, starch, and vitamins. It can be found in Southeast Asia but now has spread throughout the world, becoming a very important crop in Asia, Pacific, Africa, and the Caribbean.Taro is a neglected and underutilized species (NUS): a category of non-commodity cultivated and wild species, which are part of a large agricultural biodiversity portfolio today falling into disuse for a variety of agronomic, genetic, economic, social and cultural factors. NUS are traditionally grown by farmers in their centres of diversity, where they support nutrition security and other livelihood goals of local communities while contributing to meet their socio-cultural needs and traditional uses. Until recently these species have been largely ignored by research and development, becoming less competitive than well established major crops and losing gradually their diversity and associated traditional knowledge.